Identifying Early Developmental Profiles in Children with FXS: A Retrospective Home Videos Analysis (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
One of the major difficulties concerning Fragile X Syndrome has been early diagnosis enabling early intervention. The obstacle stems from the dismissal of signs that might raise suspicion that the syndrome is present and therefore subsequent diagnosis.The present research aims to validate a methodology employing retrospective home video analysis to explore possible early signs in children with Fragile X Syndrome. As part of this trial the videos of 6 children aged less than 30 months were analysed. We utilized a set formed by three behavioural analysis grids, mainly to analyse social attention, joint attention and sensory-motor development of said children.The retrospective home video analysis demonstrated its effectiveness in early sign identification. We verified that children with FXS had a non-social stimuli preference (e.g., prolonged visual fixation on objects), had difficulties directing attention to social stimuli (e.g., attention and response to name calling), demonstrating impairments in joint attention, and displayed prolong and repetitive interaction with objects as well as positive affective expressions. Our findings indicated that children with FXS seem to be able to discriminate between social and non-social stimuli (e.g., vocalization to people) and presented stereotypes behavior from 0 up till 30 months. Use of home videos is a potentially important methodology in identification of early sign. Identified signs from this study may serve as markers for medical referral to genetic diagnosis.